Local banking supply and private firm activity: Evidence from branch closures - Francis Haoyu Fang; Razvan Vlaicu (Inter-American Development Bank (IDB), 2024)
Private firms establish relationships with banks in local markets to obtain adequate financing for their operations through credit and loans. As major banks reduced their branch networks in recent years, many firms have lost access to their local bank. We evaluate the impact of a large number of branch closures on firm operations, wages and employment, and economic output in Brazil from 2011 to 2021. We adopt a difference-in-differences strategy with staggered treatment timing, employing both two-way fixed effects and Callaway-Sant'Anna estimators. Our study finds that bank branch closures result in a reduction in establishments with active operations from 1.2% initially to 8.1% within 4-7 years, a 0.5 decline in weekly hours of formal employment, and a compression in the real wage distribution. Micro firms, trade and service firms, and agricultural firms are found to be the most vulnerable. Our study highlights the importance of physical bank branches that provide financial access and meet the localized financial demand of several types of firms.
Keywords: G21; R11; J21; 330; Bank branch closures; Employment; Firm activity; Economic impact; Financial access; Brazil